Dynamic analysis in horizontal plane. Part II. (Rowing Biomechanics Newsletter, 2012)
The article continues discussing forces in the horizontal plain. For instance, the following questions are discussed: Could scullers use their pectorals at the catch to increase the normal component of the handle force? How can we adjust rigging to make the pulling angle straighter and reduce the axial handle force?